The Recent Behavior of Business Fixed Investment in the United States and the Role of Computers. (IMF Working Papers; Working Paper ;, 1989)
In the 1980s, U.S. real investment in high technology equipment has grown rapidly while other components of business fixed investment have been weak. The surge in real high technology investment has been accompanied by a very sharp decline in its relative price, leading to difficult index number problems. When a previously estimated model of business fixed investment was extended to cover the period through 1988, the equation for nonresidential structures performed much as before while that for producers' durable equipment substantially underpredicted recent actual outcomes. Further disaggregation revealed that the under-prediction related to the computing component.